Artikel Tinjauan: Perbandingan Metode KLT, KCKT, dan Spektrofotometri UV-VIS untuk Deteksi dan Kuantifikasi Paraben Pada Kosmetik - Hanifah Nur Widodo; Munir Alinu Mulki; Biandra Cinta Ramadhani; Salsabila Ramadani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Parabens are widely used preservatives in cosmetic products to inhibit microbial growth; however, excessive exposure has been associated with endocrine disruption and skin irritation. This study reviews and compares analytical methods used for the identification and quantification of parabens in cosmetic products, namely Thin Layer Chromatography (TLC), UV–Vis spectrophotometry, and High-Performance Liquid Chromatography (HPLC). Literature searching was conducted through PubMed and Google Scholar for studies published between 2015 and 2025. Ten articles met the inclusion criteria as original research utilizing one of the three analytical methods. TLC is effective for preliminary qualitative identification based on Rf values but is less suitable for quantitative analysis. UV–Vis spectrophotometry allows rapid determination of paraben levels within a λmax range of 254–258 nm and provides reliable results for relatively simple matrices. HPLC generally demonstrates the highest sensitivity, specificity, and accuracy, commonly employing C18 columns, methanol–aquadest mobile phases, retention times of 3–11 minutes, and high linearity (R² ≥ 0.999). Several studies also reported paraben levels exceeding the safety limits established by BPOM RI, highlighting the importance of chromatographic confirmation in cosmetic surveillance. Therefore, the selection of analytical methods should follow a fit-for-purpose approach based on analytical objectives, matrix complexity, and regulatory requirements to ensure product safety.